(untitled) (Estudos Japoneses, 2010)
The period before the Portuguese arrival in Japan, called Sengoku period，is mainly described by its political instability，uninterrupted wars and power fragmentation. Meanwhile describing the political events of the period and the Christian mission (leaded mainly by the Jesuits), this article aims to understand the relationship between this sengoku period instability and the initial acceptance, by the Japanese, of a foreigner religion.